ANALISIS PARTISIPASI MASYARAKAT DALAM PERENCANAAN STRATEGIS PENGELOLAAN AMENITAS WISATA BERKELANJUTAN - Mistriani, Nina; Indah Niati Gulo (JURNAL ILMIAH EDUNOMIKA, 2025)
In order to improve Asinan Village, Semarang Regency's tourism appeal, this study examines the critical role that community involvement plays in the administration of sustainable tourism services. Research on the dynamics and results of participatory processes in the context of rural tourism destinations is lacking, despite the growing acceptance of community-based approaches in tourism development. This study examined the strategic development and administration of sustainable tourism amenities in Asinan Village using participatory analytical techniques and a qualitative case study research design. Semi-structured interviews, focus groups, and participant observation were used in the data collection process to capture the various viewpoints and experiences of local government representatives, tourism stakeholders, and community members. By means of interpretive synthesis and theme analysis, this study reveals the intricate connections between community.